Transpacific rebalancing implications for trade and economic growth - Bosworth, Barry 1942-; Kawai, Masahiro 1947- (Brookings Institution Press, 2015)
"Examines the large imbalances in the world economy that contributed to the financial crisis of 2000-09, especially among those economies ordering the Pacific with the large deficits in the United States and the offsetting surpluses in East Asia, and how national policies could be coordinated to sustain recovery"--Provided by publisher.